Acute Aflatoxicosis in Swines in Northeastern Brazil - Olinda, Roberio Gomes; Lima, Joseney Maia; de Lucena, Ricardo Barbosa; do Vale, André Menezes; Batista, Jael Soares; de Barros, Claudio Severo lombardo; Correa, Franklin Riet; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2016)
Background: Aflatoxins are hepatotoxic mycotoxins derived from the secondary metabolism of toxigenic fungi belonging to the genus Aspergillus, especially A. flavus and A. parasiticus. Aflatoxin B1 is the most important metabolite, because of its deleterious effect mainly to the liver, especially for its carcinogenic, mutagenic and haemorrhagic properties, and usually is detected in higher concentrations in contaminated substrates. This paper reports the epidemiological, clinical, pathological and toxicological aspects of an outbreak of acute aflatoxicosis in pigs raised in Northeastern Brazil. Case: The cases occurred in a complete cycle farm, in the city of Mossoró, Rio Grande do Norte, Northeastern Brazil, in pigs ingesting low quality (moldy) corn being produced and processed on the farm. Sixty (73.1%) out of 82 two to five-months old pigs were clinicaly affected and 54 (65.8%) died. All animals showed fever, weight loss, tachycardia, tachypnea, lethargy, muscle tremors, muscle weakness and diarrhea. The clinical course ranged from five to 48 hours. Adult pigs were not affected. At necropsies, generalized jaundice, ascites, hydropericardium, petechial hemorrhages in the mesentery, subcutaneous edema and mesocolon were observed. The liver was yellow-orange with reddish diffuse multifocal areas, enlarged and extremely friable. Histologically there was swelling of hepatocytes with severe diffuse hepatocellular fatty degeneration, centrilobular hepatocellular necrosis, proliferation of bile ducts and cholestasis. High concentrations of aflatoxin B1 were determined in the corn (3400 μg/kg) and ration (1460 μg/kg). Discussion: The diagnosis of aflatoxicosis was based on epidemiological investigation associated with clinical and pathological findings and confirmed by high levels of aflatoxin B1 found in samples of corn and feed. Of the numerous types of aflatoxin reported, the most common is the B1, which is typically produced by Aspergillus fungi. In intensive pig farms, management conditions increase the chances of occurrence of intoxications caused by the poor quality of the grain (especially maize) by the poor quality of the grain (especially maize) used in the diet formulation. In the present report the corn was severely degraded and kept in physical conditions that favor the proliferation of aflatoxins. In addition, young animals, which are more suseptible, were the only ones affected with 73% morbidity and 65.8% mortality. In cases of spontaneous aflatoxicosis morbidity in pigs can vary from 10 to 100% and mortality is high when the diet has a high concentration of aflatoxins as observed in this outbreak (3400 and 1460 μg/kg of B1 in corn and food, respectively) . Increases in sérum ALT levels indicate hyperacute, acute or chronic active hepatocellular damage; a toxic hepatitis in this case. Furthermore, the increased serum AST suggest the existence of extensive and progressive hepatocellular damage, because this enzyme is synthesized mitochondrial level. Legislation in Brazil, determines that the maximum tolerated aflatoxin concentrations are 50 parts per million (ppm) or 50 μg/kg in food included in the diet formulation for animal consumption and 20 ppb in corn grain for human consumption. Differential diagnosis of aflatoxicosis include leptospirosis and intoxication by Crotalaria retusa or other pyrrolizidine alkaloids-containing plants. Keywords: aflatoxicosis, mycotoxins, toxic hepatitis, swine.